A century of parasitology : discoveries, ideas, and lessons learned by scientists who published in the Journal of Parasitology, 1914-2014 /: discoveries, ideas, and lessons learned by scientists who published in the Journal of Parasitology, 1914-2014. ([2016]) - Unknown
No abstract available